AgriFoodPy: a package for modelling food systems - Cordero, Juan P.; Donkers, Kevin; Harrison, Ian; Bridle, Sarah L.; Frankowska, Angelina; Cain, Michelle; Ward, Neil; Frendenburgh, Jez; Pope, Edward; Kluczkovski, Alana; Schmidt, Ximena; Silva, Jacqueline; et al. (The Open Journal, 2024)
AgriFoodPy is an open-source Python package for processing, simulation, and modeling of agrifood datasets and systems. By employing xarray (Hoyer & Hamman, 2017) as the primary data structure, AgriFoodPy provides methods to manipulate tabular data by extending xarray functionality via accessor classes. It acts as an accessibility and interoperability layer between data sources and external packages, and also bundles with a library of models for use without any additional requirements. A separate repository, agrifoodpy_data, is actively maintained in parallel to provide access to local and global agrifood datasets, including geospatial land use and classification data (Morton, 2022), food supply (FAO, 2023), life cycle assessment (Poore & Nemecek, 2018), and population data (United Nations, 2022). The AgriFoodPy framework is region-agnostic and provides facilities to model and simulate processes and intervention impacts regardless of their geographic origin.
Keywords: 46 Information and Computing Sciences